Implementation of Criminal Sanctions as Ultimum Remedium in Article 100 of Law Number 32 of 2009 concerning Environmental Protection and Management - Dedi Rustandi; Happy Yulia Anggraeni (Jurnal Ilmiah Dunia Hukum, 2025)
Criminal law enforcement against environmental violations serves as the last step (ultimum remedium) used when administrative sanctions are proven to be unable to stop violations. This study aims to analyze the application of the principle of ultimum remedium and assess the suitability of the application of Article 100 paragraphs (1) and (2) in Law Number 32 of 2009 concerning Environmental Protection and Management in cases of environmental pollution carried out by PT. Trisan Abadi. This study uses a normative juridical method with a case study approach. The results of the study show that the relevant agencies have first issued administrative sanctions through Decree Number 660.31/Kep.412-DLH/2020. However, because business actors do not comply with the sanctions and violations occur again, criminal sanctions are then imposed. The application of the articles used has met the elements of the law, including the imposition of responsibility on corporations as legal subjects. These findings show that although the principle of ultimum remedium has been implemented in accordance with the provisions, its effectiveness still needs to be improved through stricter supervision, training for law enforcement officials, and inter-agency synergy. These measures are important to have a deterrent effect and ensure sustainable environmental protection.